ANALISIS KALIMAT IMPERATIF PADA TUTURAN MASYARAKAT DESA TELUK RAYA KECAMATAN KUMPEH KABUPATEN MUARO JAMBI (KAJIAN PRAGMATIK) - Sainil Amral; Siti Dian Ulfah (Universitas Batanghari, 2019)
The purpose of this research is to describe the form imperative sentences in the oral speech of the Teluk Raya village society, Kumpeh Regency Muaro Jambi (A Pragmatic study). This research is descriptive qualitative. The primary data is taken from the Imperative sentences (order) of Malay Jambi Kumpeh language on the community of Teluk Raya Village Kumpeh Muaro Jambi district, while the secondary data is derived from books. In collecting the data, uninvolved conversation observation technique, note-taking technique, and interview technique are used. Based on the results of the data analysis, it can be concluded that there are five imperative sentences of the Jambi Malay Kumpeh language. They are ordinary imperative sentence, request imperative sentence, granting permit imperative sentence, ask and order imperative sentence. Moreover, there are also three kinds of speech acts occur in the Jambi Malay language, they are locutionary, illocutionary, and perlocutionary.